Critical Anachronism: The recovery of the everyday in the context of Non-objective painting - Spremberg, Alexander (Curtin University, 2017)
This research specifically describes how a non-objective inspired painting practice can facilitate the innovation and expansion of knowledge in an area of under-examined cultural terrain, and specifically, what theories, materials and processes pertaining to the discourse of the everyday are best used to concretely investigate this context. Ultimately, the new concept of ‘critical anachronism’ as a form of artistic engagement is presented herein.